\(\dfrac{a}{b}=\dfrac{c}{d}\) chứng minh
a)\(\dfrac{a^2-b^2}{c^2-d^2}=\dfrac{ab}{cd}\)
b)\(\dfrac{\left(a-b\right)^2}{\left(c-d\right)^2}=\dfrac{ab}{cd}\)
c)\(\left(\dfrac{a+b}{c+d}\right)^3=\dfrac{a^3-b^3}{c^3-d^3}\)
d)\(\dfrac{5a+3b}{5c+3d}=\dfrac{5a-3b}{5c-3d}\)
Lời giải:
Đặt $\frac{a}{b}=\frac{c}{d}=k\Rightarrow a=bk; c=dk$
a. Ta có:
$\frac{a^2-b^2}{c^2-d^2}=\frac{(bk)^2-b^2}{(dk)^2-d^2}=\frac{b^2(k^2-1)}{d^2(k^2-1)}=\frac{b^2}{d^2}(1)$
$\frac{ab}{cd}=\frac{bk.b}{dk.d}=\frac{b^2}{d^2}(2)$
Từ (1); (2) ta có đpcm
b.
$\frac{(a-b)^2}{(c-d)^2}=\frac{(bk-b)^2}{(dk-d)^2}=\frac{b^2(k-1)^2}{d^2(k-1)^2}=\frac{b^2}{d^2}(3)$
Từ $(2); (3)$ suy ra đpcm
c.
$(\frac{a+b}{c+d})^3=(\frac{bk+b}{dk+d})^3=(\frac{b(k+1)}{d(k+1)})^3=\frac{b^3}{d^3}(4)$
$\frac{a^3-b^3}{c^3-d^3}=\frac{(bk)^3-b^3}{(dk)^3-d^3}=\frac{b^3(k^3-1)}{d^3(k^3-1)}=\frac{b^3}{d^3}(5)$
Từ $(4); (5)$ ta có đpcm
d. Làm tương tự.